173TiP PECan study, imaging PD-L1 in cancer: A tool for measuring response to immunotherapy?. (15th December 2019) - Hughes, D J; Chand, G; Josephs, D; Harries, M; Papa, S; Spicer, J; Ting, H H; Goh, V; Cook, G
Abstract: Background: Cancer evades immune detection and destruction via upregulation of immune checkpoint molecules, such as programmed death-1 (PD-1). Signalling from these molecules can be inhibited by antibodies targeting them or their ligands (e.g. PD-L1). Durable responses have been demonstrated, for example, in subsets of patients with melanoma or non-small cell lung cancer (NSCLC). Identifying potential 'responders' remains challenging, with immunohistochemical PD-L1 expression the only validated biomarker to date. Biopsies are however invasive, do not account for intratumoural heterogeneity nor are practical for serial measurement, and therefore cannot be used to measure response to immunotherapy reliably. Radioisotope labelling and imaging of PD-L1 antibodies has been shown in preclinical (indium-111) and phase I clinical trials (technetium-99m ( 99m Tc)) to demonstrate PD-L1 expression in tumours. It has the potential to capture heterogenous expression, as well as spatiotemporal variance which would permit quantitative assessment of expression and serve as a companion diagnostic and monitoring tool to improve patient stratification and outcomes. Trial Design: The PECan (PD-L1 Expression in Cancer) study aims to determine whether PD-L1 expression measured using 99m Tc-labelled PD-L1 single-domain antibody single photon emission computed tomography (SPECT) in melanoma and NSCLC correlates with, and thus can predict treatment response in those having anti-PD1/PD-L1 immunotherapy. 99m Tc-PD-L1 SPECT will be compared with standard FDG-PET/CT at 0, 12 and 24 weeks in 15 patients with melanoma and FDG-PET/CT and standard CT at 0, 9 and 18 weeks in 15 patients with NSCLC. Imaging will be analysed centrally by an experienced nuclear medicine physician and correlated with clinical data. PD-L1 expression, assessed using SPECT, will also be correlated with baseline immunohistochemistry to determine intertumoural PD-L1 heterogeneity. Patients will require confirmed histological status, PD-L1 assessment and not have received any prior systemic anti-cancer therapy nor radiotherapy. This study is now open to recruitment with reporting expected late 2020. Clinical trial identification: UK IRAS ID 256684. Legal entity responsible for the study: King's College London and Guy's and St Thomas' NHS Foundation Trust. Funding: Department of Cancer Imaging, King's College London, UK with funding from NanoMab Technology Limited, China. Disclosure: G. Chand: Advisory / Consultancy, Shareholder / Stockholder / Stock options: NanoMab Technology Limited. H.H. Ting: Leadership role, Shareholder / Stockholder / Stock options, Full / Part-time employment, Officer / Board of Directors: NanoMab Technology Limited. G. Cook: Research grant / Funding (institution): NanoMab Technology Limited. All other authors have declared no conflicts of interest.